The Influence of Sustainable Building Materials in Malaysia - Hashim, Nurulhuda; Tay, Pei Ying (MAJ - Malaysia Architectural Journal, 2023)
The increased in population growth entails more houses and buildings worldwide. These activities utilize materials, land and thus had resulted in the depletion of natural resources. Hence, the evolution of building material has shifted towards less sustainable manmade materials which has open the gateway to a massive carbon footprint where world leaders are trying to address today. Over the past decade, there have been signs that global climate change is occurring rapidly and might be accelerating too. The climate change had brought significant changes that are catastrophic to the environment and had disrupted the daily lives of humans. Thus, community awareness and concern for the environment have emerged amongst humans to incorporate environmental sustainability practices especially in the construction industry. This increased attention drives the Malaysia’s government and professional organizations to be more aggressive on the adoption of sustainable construction. The purposed of the research is to promote a more extensive usage of sustainable building materials towards a more sustainable approach of the construction industry in Malaysia by identifying what are the available sustainable building materials in the country, understanding why it is important to use such materials and by finding out what are the challenges in using these green building materials. The methodology used for this research is quantitative research as the target population of the study is large. Questions are being established in the questionnaire surveys through Google survey forms and then distribute it to the target respondents to obtain primary data. Based on the findings, it indicates that cost issue is the main concern of the challenges faced by architects in Klang Valley. In conclusion, the study found out that the challenges in implementing sustainable building materials outweigh the benefits of using these materials.